A comparison of changes in stable isotope ratios in the epidermal mucus and muscle tissue of slow‐growing adult catfish. Issue 4 (3rd October 2016) - Maruyama, Atsushi; Tanahashi, Emi; Hirayama, Takanobu; Yonekura, Ryuji
Abstract: Although stable isotope analysis is a powerful tool for determining diet, migration patterns and the structure of food webs in aquatic systems, the slow response of isotopic ratios in the widely used muscle tissue often hampers this approach, particularly in slow‐growing or adult fishes. We conducted a diet‐switch experiment to compare the changes in the stable carbon isotope ratio (δ 13 C values) in the epidermal mucus and muscle tissue of five‐year‐old catfish ( Silurus asotus ). The isotope ratios in noninvasively sampled mucus changed more rapidly than those in the muscle tissue. As isotopic change in mucus was relatively rapid, this technique can be used over a finer timescale than traditional isotopic analyses using the muscle tissue. The isotopic change half‐life in our experimental condition was 200 days, which would not be short enough for some research purposes. Examining mucus along with the muscle would enable food habits of slow‐growing fishes to be determined over different timescales. However, the rate of isotopic change in the mucus was negatively affected by the size of fish and was slower than the previously reported rates in juvenile steelhead. These findings suggest that mucus turnover rates need to be determined prior to the field data interpretation.